Benthic foraminifera diversity from the south Atlantic Ocean: Tierra del Fuego and surrounding waters (South America) - Perez, Silvina Raquel (2024)
The present study provides a detailed record of foraminiferal fauna and their ecological implications from surface sediments from Atlantic shelf of Tierra del Fuego, Argentina. The foraminiferal assemblage is mostly composed by four main hyaline genera, such as Cibicidoides, Cibicides, Globocassidulina and Buccella, which allowed the identification of three environmental zones. Zone 1 (Z1, 37 to 90 m) encompasses the eastern Beagle Channel and San Sebastian Bay. The assemblage reflected well oxygenated marine inner shelf habitat, adapted to cold temperate waters. Zone 2 (Z2, up to 98.4 m), is located around the southern tip of Tierra del Fuego. The assemblage suggested a deeper marine environment, well oxygenated and with higher energy, probably due to the effect of tides and mainly by the influence of Malvinas Current. Finally, Zone 3 (Z3, up to 195 m) is located furthest from the Atlantic coast and the assemblage suggested an environment characteristic of outer shelf, with well oxygenated cold waters and high-energy environment, reflected by species adhered to the substrate and coarse sediments. The distribution and abundance of certain species showed the influence of the Malvinas Current, while others evidenced a contribution of the Cape Horn waters.